A packed bed membrane reactor for production of biodiesel using activated carbon supported catalyst - Baroutian, S.; Aroua, M.K.; Abdul Raman, Abdul Aziz; Sulaiman, N.M.N. (2011)
In this study, a novel continuous reactor has been developed to produce high quality methyl esters (biodiesel) from palm oil. A microporous TiO2/Al2O3 membrane was packed with potassium hydroxide catalyst supported on palm shell activated carbon. The central composite design (CCD) of response surface methodology (RSM) was employed to investigate the effects of reaction temperature, catalyst amount and cross flow circulation velocity on the production of biodiesel in the packed bed membrane reactor. The highest conversion of palm oil to biodiesel in the reactor was obtained at 70 degrees C employing 157.04 g catalyst per unit volume of the reactor and 0.21 cm/s cross flow circulation velocity. The physical and chemical properties of the produced biodiesel were determined and compared with the standard specifications. High quality palm oil biodiesel was produced by combination of heterogeneous alkali transesterification and separation processes in the packed bed membrane reactor. (C) 2010 Elsevier Ltd. All rights reserved.